2014
DOI: 10.1017/s1473550414000056
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of cyanobacteria inhabiting rocks with different light transmittance in the Mojave Desert: a Mars terrestrial analogue

Abstract: The Mojave Desert has been long considered a suitable terrestrial analogue to Mars in many geological and astrobiological aspects. The Silver Lake region in the Mojave Desert hosts several different rock types (talc, marble, quartz, white carbonate, and red-coated carbonate) colonized by hypoliths within a few kilometers. This provides an opportunity to investigate the effect of rock type on hypolithic colonization in a given environment. Transmission measurements from 300 to 800 nm showed that the transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 31 publications
2
30
1
Order By: Relevance
“…Cyanobacteria photosynthetic activity is essential for endolithic communities and, therefore, the light intensity and wavelengths reaching the colonization zone within the endolithic habitats could be a limiting factor (Nienow et al ., ; Boison et al ., ; Smith et al ., ; Raanan et al ., ). Extremely high solar fluxes were measured in the VL and MTQ locations (up to 2554 µmol photons m −2 s −1 ) but rock substrates have the capacity of drastically attenuating incident light and stopping harmful UV radiation (Berner and Evenari, ; Oren et al ., ; Matthes et al ., ; Hughes and Lawley, ; Horath et al ., ; Amaral et al ., ; Hall et al ., ; Cockell et al ., ; Cowan et al ., ; Smith et al ., ; Wierzchos et al ., ). The spectral data we obtained for our four rock substrates revealed that light transmission was inversely correlated with depth of colonization.…”
Section: Discussionmentioning
confidence: 97%
“…Cyanobacteria photosynthetic activity is essential for endolithic communities and, therefore, the light intensity and wavelengths reaching the colonization zone within the endolithic habitats could be a limiting factor (Nienow et al ., ; Boison et al ., ; Smith et al ., ; Raanan et al ., ). Extremely high solar fluxes were measured in the VL and MTQ locations (up to 2554 µmol photons m −2 s −1 ) but rock substrates have the capacity of drastically attenuating incident light and stopping harmful UV radiation (Berner and Evenari, ; Oren et al ., ; Matthes et al ., ; Hughes and Lawley, ; Horath et al ., ; Amaral et al ., ; Hall et al ., ; Cockell et al ., ; Cowan et al ., ; Smith et al ., ; Wierzchos et al ., ). The spectral data we obtained for our four rock substrates revealed that light transmission was inversely correlated with depth of colonization.…”
Section: Discussionmentioning
confidence: 97%
“…These communities have been reported from many hot deserts including the Mojave (Schlesinger et al 2003;Smith et al 2014), Atacama (Warren-Rhodes et al 2006;Azúa-Bustos et al 2011;Lacap et al 2011), Negev (Friedmann et al 1967;Berner and Evenari 1978;Wierzchos et al 2012) and Namib (Stomeo et al 2013) and in other semiarid and hyperarid regions (Tracy et al 2010;Pointing et al 2007;Wong et al 2010;Weber et al 2013). …”
Section: Introductionmentioning
confidence: 91%
“…3B shows the green biofilm of cyanobacteria that live beneath translucent rocks in many deserts surviving on as little as a few days of rain or fog each year (32)(33)(34). The example shown is from an unusual carbonate rock from the Mojave Desert that is clear inside but covered with a red coating (35,36). Fig.…”
Section: Strategy For Exoplanetsmentioning
confidence: 99%